Comparison of Performances Between Two-stage and Single-stage L-Band EDFA - Harun, Sulaiman Wadi; Tamchek, Nizam; Ahmad, Harith (De Gruyter, 2003)
Gain enhancement in a long wavelength (L-band) erbium-doped fiber amplifier (EDFA) using a two-stage configuration with dual forward pumping scheme is demonstrated. Compared to a conventional single-stage amplifier, the two-stage amplifiers can improve the small signal gain over the wavelength region from 1560 to 1612 nm. A maximum gain enhancement of 9.6 dB is obtained for a two-stage type II amplifier at the signal wavelength of 1568 nm. The corresponding noise figure is also improved by 0.2 dB.